The Use of Classroom Questioning Strategy in Teaching Speaking Abiliy at UPT SMA Negeri 4 Parepare - Putri Saskia; Sudarmanto (La Parole : Journal of Language Teaching and Pedagogy, 2022)
The purpose of this study is to improve students' speaking skill because the questioning strategy method is a good method to improve students' speaking skill, students' confidence is also better able to build, students are also able to be more active in class and learning in English. The researcher conducted research at UPT SMA Negeri 4 Parepare with a total of 20 students which was taken as sample and used total sampling. The results of the data analysis of students’ mean score obtained by the researchers during the research were is 52.5 pre-test and 79.65 in post-test. Students’ speaking skill in class XIPA 4 at UPT SMA Negeri 4 Parepare are improved after being taught using questioning strateg. It is improved by the result of t-test where H0 is rejected and HI is accepted.